MEKK3 is essential for lipopolysaccharide-induced interleukin-6 and granulocyte–macrophage colony-stimulating factor production in macrophages - Kim, Kihwan (Blackwell Science Inc, 2007)
Mitogen-activated protein/ERK kinase kinase 3 (MEKK3) is a Ser/Thr protein kinase belonging to the MEKK/STE11 subgroup of the MAP3K family. Recently, we found that MEKK3 plays a critical role in interleukin-1 (IL-1) receptor and Toll-like receptor 4 signalling using established primary mouse embryonic fibroblast (MEF) cell lines. However, the function of MEKK3 in immune cells has not been studied because germ-line MEKK3 knockout mice are embryonically lethal between embryonic days 10 and 11. In this study, we used small interference RNA to the mouse Mekk3 gene to specifically knock down MEKK3 expression in the macrophage line Raw264.7. We found that the lipopolysaccharide-induced IL-6 and granulocyte-macrophage colony-stimulating factor (GM-CSF) production was dramatically decreased in MEKK3 knockdown cells whereas the tumour necrosis factor-α and IL-1β production were not affected. We also observed that the ERK1/2, p38 and JNK MAPK induction in MEKK3 knockdown cells were moderately inhibited within the first 60 min of stimulation, while the ERK and p38 were more severely inhibited after 2–4 hr of stimulation. Degradation of IκBα was also partially blocked in MEKK3 knockdown cells. Notably, the impairment in IL-6 and GM-CSF production in the MEKK3 knockdown cells was restored by reintroducing a human Mekk3 cDNA that could not be targeted by mouse Mekk3-siRNAs. In conclusion, this study showed that MEKK3 is a crucial and specific regulator of the proinflammatory cytokines IL-6 and GM-CSF in macrophages and provided a novel method for investigating MEKK3 function in other immune cells.